A ratiometric fluorescent sensor for detection of metformin based on terbium–1, 10-phenanthroline–nitrogen-doped-graphene quantum dots. Issue 34 (10th August 2022) - Gazizadeh, Masoud; Dehghan, Gholamreza; Soleymani, Jafar
Abstract : Shcematic representation of the MTF detection by an enhancing mechanism. Abstract : Metformin (MTF), an effective biguanide and oral antihyperglycemic agent, is utilized to control blood glucose levels in patients with type II diabetes mellitus, and the determination of its concentration in biological fluids is one of the main issues in pharmacology and medicine. In this work, highly luminescent nitrogen-doped graphene quantum dots (N-GQDs) were modified using terbium (Tb 3+ )–1, 10-phenanthroline (Phen) nanoparticles (NPs) to develop a dual-emission ratiometric fluorescent sensor for the determination of MTF in biological samples. The synthesized N-GQDs/Tb–Phen NPs were characterized using different techniques to confirm their physicochemical properties. The N-GQDs/Tb–Phen NPs showed two characteristic emission peaks at 450 nm and 630 nm by exciting at 340 nm that belong to N-GQDs and Tb–Phen NPs, respectively. The results indicated that the emission intensity of both N-GQDs and Tb–Phen NPs enhanced upon interaction with MTF in a concentration-dependent manner. Also, a good linear correlation between the enhanced fluorescence intensity of the system and MTF concentration was observed in the range of 1.0 nM–7.0 μM and the limit of detection (LOD) value obtained was 0.76 nM. In addition, the prepared probe was successfully used for the estimation of MTF concentration in spiked human serum samples. In conclusion, the reported dual-emission ratiometric fluorescent sensor can be used as a sensitive and simple fluorimetric method for the detection of MTF in real samples.